PENGARUH UTANG USAHA DAN SUKU BUNGA KREDIT TERHADAP KINERJA PT. MARTINA BERTO, TBK. (2007 – 2018) - Francisca Sestri Goestjahjanti (Universitas Bunda Mulia, 2020)
The growth of the business in the last few years has stagnated, tends to decline its sales performance due to the trade crisis between China and America. However, the Cosmetics industry in Indonesia is predicted to grow approximitely 9 percent, only enjoyed by companies who ready to use industry 4.0. This global change and digital era causes a negative impact on the sales performance of PT. Martina Berto, Tbk. recent years. The purpose of this study is to determine a partially and simultaneously influence between account payable and loan interest rates on company performance. Explanatory research methods in this study has been done through hypothesis test, and uses a simple and multiple linear regression with SPSS software version 22 as an analysis technique. Secondary data of this study showed n = 12, of time series data from 2007up to 2018. The results of this study is indicate that partially there is a significant, positive influence is 63.50% between Accounts Payable (X1) on Company Performance (Y), and that partially there is a significant, negative effect is 38.30% between Loan interest rates (X2) on the Company's performance (Y). And a simultaneously, there is a significant, positive effect is 74,40 %, a very strong relationship, between Accounts Payable (X1) and Loan interest rates (X2) on Company Performance of PT. Martina Berto, Tbk. (Y).